Mapping the Potential Use of Peat Land to Formulate a Management Strategy for Smallholder Palm Oil Plantations - Rini Hazriani; Shenny Oktoriana; Romiyanto (Jurnal Ilmu Pertanian Indonesia, 2026)
By 2030, smallholder plantations will account for 60% of the total oil palm plantation cover. Currently, 40% of smallholder oil palm farms in Indonesia have low productivity and are located in peatlands. The result is that increasing land productivity requires taking into account the maturity, thickness, and depth of the groundwater table. The study's goals were to identify many characteristics of peatlands in smallholder plantations, to create a map of potential peatland use, and to build a strategy for smallholder oil palm farms based on peat potential maps. The peatland mapping units was determined on a combination of soil type maps, peat maturity maps, and peat thickness maps. Observations and extra sampling at each land mapping unit (LMU) were conducted using a random survey method to stratify 20 observation sites and soil physical property samples. The strategy formulation technique employed a SWOT analysis, which was evaluated by key informants. The study found that (1) the characteristics of peat in each LMU show relatively similar properties, namely having low bulk density, high groundwater content, and porous porosity, (2) there were 5 LMUs based on maturity, thickness, and groundwater level, and (3) the strategy consists of efforts to improve the quality of the water management system to overcome the depth of the groundwater level that exceeds the required limit, overcome the depth of irrigation channels that exceed the maximum depth, increase the use of fertilizer according to the recommended dose to increase oil palm production.